Detector design and performance tests of the ESS-neutron Beam Loss Monitor detectors. (1st January 2023) - Segui, L.; Dolenc Kittelmann, I.; Papaevangelou, T.; Aune, S.; Benedetti, F.; Gougnaud, F.; Lahonde, C.; Legou, P.; Mariette, Y.; Marroncle, J.; Mikulec, B.; Nadot, V.; et al.
Abstract: A new type of beam loss monitor has been developed based on the detection of fast neutrons produced by beam losses in hadron linear accelerators. This neutron sensitive Beam Loss Monitor (nBLM) has been concieved to fulfil the requirements of the European Spallation Source (ESS) and it will be part of the ESS neutron sensitive BLM system (ESS-nBLM). It has been specifically designed for the low energy part, where only neutrons and gammas produced by the loss can exit the accelerator vessel. Here other types of BLM, based on charged particle detection, suffer from the lack of signal compared to the photon background induced by the radio-frequency cavities. However, it can also be operated in regions of higher energy. The detector is of the Micromegas type and have been designed at IRFU to be able to detect fast neutrons while having a small sensitivity to gammas and thermal neutrons. In this work we focus on the proof of neutron-to-gamma rejection and the first operation of the detector in real beam conditions during the commissioning of LINAC4 (CERN). Controlled beam losses were provoked and have been detected by the nBLM detector installed, demonstrating also the discrimination of the neutron signal from RF x-ray background.